Risk assessment methodology for the forniture industrial sector - Rodrigues, Matilde A. (My University, 2014)
Companies need to constantly make decisions about risk. They need to decide if a certain risk level is low enough or if some measures for its reduction are still needed. In this regard, risk assessment appears as a basis for the decision-making about risks. However, risk acceptance is an important issue related to the risk assessment process, which may put into question its appropriateness. Despite the importance of risk acceptance, this subject is insufficiently discussed in the literature regarding occupational settings. In the Portuguese reality, Occupational Safety & Health (OSH) practitioners develop the risk assessment process in a different way. In addition, despite acceptance criteria have been considered important, its definition is considered to be a difficult step, leading them to use the criteria pre-defined in the risk assessment methodologies available. However, in some cases, the criteria included in these methodologies are not adjusted to the reality where they will be applied. Therefore, in order to improve the risk assessment process at the furniture sector, a new methodology was proposed. In a first stage, the acceptance criteria to be used in assessing the occupational risks in the industrial furniture sector were developed and presented as acceptable and tolerable thresholds. After that, they were integrated in a risk matrix. We believe that this new method could be a good approach to support risk decisions in these settings.
Keywords: Gestión del riesgo; Risk Management; Risk Assessment; Forniture Industrial Sector; Risk Assessment Methodology; Health and Safety